Assessment of macro-, meso- and microplastics in wild and cultivated Perna perna mussels (Mollusca: Bivalvia) - Lucas Aguiar Leal Rocha; Helena Antunes Portela; Mônica Regina da Costa Marques Calderari; Fábio Vieira de Araújo (Scientia Marina)
Microplastics have drawn significant interest within the scientific community due to their environmental impact. In marine ecosystems, these particles readily absorb toxic substances and, because of their microscopic size, are consumed by various organisms that are eventually incorporated into the human food chain. Several studies emphasize this unintentional transfer to human foods. To investigate microplastic contamination in Perna perna mussels sold commercially, wild (harvested from the coastal environment) and farm-raised (cultivated) samples were purchased from local markets in Niterói, RJ, Brazil. One kilogram of each type was processed through digestion in an NaOH 5% solution and then analysed to assess the quantity and types of microplastics present. Both wild and cultivated mussels contained microplastic film and fibres, with 145 items (0.145 items g⁻¹) identified in wild specimens [67% nylon (polyamide) and 33% polyethylene] and 120 items (0.120 items g⁻¹) in cultivated mussels (100% polyamide). The microplastics varied in size, ranging from 0.45 μm to 28 mm, with the most common colours being black, blue and transparent. These findings highlight the potential risks of consuming these organisms regardless of their source and the need for further investigation into the effects of these pollutants on human health.